Restructuring Canada's health systems : proceedings of the Fourth Canadian Conference on Health Economics - Deber, Raisa, B.; Thompson, Gail, G. (Heritage., 1992)
The papers, collected in this volume, consider a wide range of fundamental issues related to health care policies and structures.